TARIAN SPIRITUAL JALALUDDIN RUMI - Eni Murdiati (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2011)
The Whirling Dervishes (The Darwisy the Round and round) or Sama’. The term used by the Maulawiyah or Jalaliyah adherents of this, by doing a dance around in circles, accompanied by drums and flute, in the devotions they are to reach ecstasy. Rumi and the legendary spiritual dance into a work of great almighty to fill in a drought spitual man approached the Creator.